TREATMENT OF VASCULAR LESION OF LIP WITH 980NM DIODE LASER COMPARED WITH CONVENTIONAL METHOD - Bardhoshi, Merita; Gutknecht, Norbert; Xhajanka, Edit; Bardhoshi, Esat; Hysenaj, Neada (European Scientific Journal, ESJ, 2014)
Introduction: Mulliken and Glowacki introduced a simple classification in 1982 that was based on the clinical, histochemical and cellular criteria to distinguish between the various vascular anomalies. They described two distinct entities which are haemangiomas and vascular malformations. Hence, they can be situated at different area of the oromaxillofacial region: tongue, lip, palate, buccal mucosa, and gingiva. Numerous method of treatment has been used such as cryotherapy, embolization, sclerotisation, cold scalpel and combination of these. Management of these lesions with laser is an option, and several laser systems have been developed using principles of selective photothermolysis. Thus, the clinical cases presented in this study are treated with 980 nm diode laser. Material and methods: In this study, we reported 60 cases with vascular lesions of lip treated in the Dental Clinic of the University of Tirana from May 2007 to May 2012. 30 cases were treated with 980 nm diode laser and 30 cases with scalpel. Thus, the operative treatment and post-operative follow-up for the evaluation of early and long term results was documented. All statistical test and graphics were created using SPSS for Medical Calculation (MedCalc). Data were expressed as mean –standard deviation and 95 % confidence interval and the statistical significance was estimated by Student´s t-test and p values< 0,05 were considered significant. Results: According the protocol research, the results of the two groups of population were compared as laser group and the control group. Diode laser surgery was rapid and bloodless. The wounds were healed without complications in two to three weeks depending on the size of the lesions. The parameters evaluated are: bleeding, pain, swelling, scar formation, functional disturbance, and recurrence. On the basis of the data collected from the laser group, no pain, or swelling were reported during the first week after intervention and from the control group, 22 of the patients reported pain and 20 referred swelling after the surgical excision. After one month of the treatment, no scar formation was reported from laser group and in the patients of control group, scarring was observed in the site of the performed excision. After 3 years of follow-up, no recurrence was recorded after laser surgery versus one case was treated with scalpel during the first year. No functional disturbance was recorded from the laser group versus 6 cases reported from the control group. Conclusion: 980 nm is a good modality for the treatment of vascular lesion of lip. This treatment provides satisfactory results, and is well accepted by all patients without compromising their health and functionality.